Joinson’s Facebook Questionnaire: Italian adaptation and validation - Amelia RIzzo; Martina Barbera; Martina Commendatore; Giulia Marafioti; Maria Grazia Maggio (Advances in Medicine, Psychology, and Public Health)
Introduction: Studies on motivations and uses of social network sites (SNS), with particular reference to Facebook, have increasingly developed in the last decade. Nevertheless, there are still very few valid measures for Facebook activity, especially in Italian. The study aims to propose an Italian instrument, developed starting from Joinson’s Facebook Questionnaire, and to verify its psychometric properties to provide researchers with a valid measure for the target population. Methods: Three hundred fifty-five subjects, 185 males and 170 females, aged 9 to 45 years (M = 23,14 ± 6.22), were individually interviewed with the Italian version of the Facebook Questionnaire. Results: Exploratory factor analysis revealed a 7-factor latent structure, similar to the original study, which explained 52% of the variance and obtained a Cronbach's alpha value of .84. and different uses according to the life stage. Conclusions: Methodological implications and cues for future research are discussed.